Upgrading of HMF and Biomass‐Derived Acids into HMF Esters Using Bifunctional Ionic Liquid Catalysts under Solvent Free Conditions. Issue 22 (13th June 2018) - Kumar, Komal; Dahiya, Aditi; Patra, Tanmoy; Upadhyayula, Sreedevi
Abstract: Catalytic conversions of biomass‐derived compounds like 5‐hydroxymethylfurfural (HMF) and levulinic acid (LA) to value‐added compounds have drawn tremendous interest in recent years. In this study, we report the catalytic upgrading of HMF into HMF levulinate and HMF esters under solvent‐free condition using laboratory‐synthesized bifunctional ionic liquid (IL) catalysts. The synthesized ILs were characterized using 1 H NMR and 13 C NMR spectroscopy. Pyridine Fourier transform Infrared spectroscopy (FT‐IR) studies were carried out for their detailed Brønsted and Lewis acidity characterization. Catalytic activity of these ILs was tested in the conversion of HMF into HMF levulinate in the temperature range of 75 to 120 °C and 5 h reaction time using 150 mg each of IL catalyst and 4 Å molecular sieves with LA to HMF molar ratio of 5:1. It was found that strong dual acidic catalyst [SMIM][FeCl4 ] was found to exhibit highest catalytic activity with 97.0% HMF conversion and 78.1% yield of HMF levuliante. Catalytic activity decreased in the order: [SMIM][FeCl4 ]> [BSO3 HMIm][FeCl4 ]> [SMIM][Cl]> [BSO3 HMIm][Cl]> [BMIM][FeCl4 ]> [BMIM][Cl]. The reaction parameters such as reaction time, temperature, mole ratio of the reactants, and effect of catalyst loading were optimized.The recyclability of these bifunctional catalysts was also tested and found to be intact for three recycles. Abstract : Herein, biomass derived platform chemical, like 5‐Hydroxy methyl furfural and acids were successfully upgraded into HMF esters, using bifunctional ionic liquid catalyst under solvent free conditions. Synthesis of HMF levulinate and other HMF esters under solvent free condition devoid the use of any harmful solvents which favor environmental benign condition. Synthesized HMF levulinate can be used as fuel additives, surfactants and fungicides.